Perancangan Sistem Informasi Akuntansi Harga Pokok Produksi Pada Distro Viking Cimahi Dengan Menggunakan Software Microsoft Visual Basic 2008 Dan Database MySQL - Sheylla Febryani; Dony Waluya Firdaus (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2019)
Viking Distro cimahi conducts business in manufacturing companies that produce t-shirts for Persib bandung soccer players, researchers conducted a survey and found that the accounting records system that is currently running is still manual, therefore researchers conducted research with the title " Designing a Cost of Production Accounting Information System (HPP) on the Viking Cimahi Distro using Mcrosoft Visual Basic 2008 and the MYSQ Database ". Researchers conduct research using research design that is descriptive research, the type of research using academic research, data using quantitative data, while the research method is survey and conduct interview interviews to collect data according to the surveyed, while researchers in designing using contex charts, data flow diagram and flowchart system The researcher conducts research by making a system of accounting information on the cost of production, with the design can provide input related to the title that the researcher discussed.